Investigation of Effects of Process Variables on Weld Bead Characteristics in Surface Coating of 309L Stainless Steel by Wire Arc Additive Manufacturing - Van Thuc Dang; Van Thao Le; Trung Thanh Nguyen; Van Luu Dao (Advances in Technology Innovation, 2025)
Coating carbon steel surfaces with stainless steel is a crucial technology in various industries to extend the product lifespan. This study focuses on investigating the effects of process parameters on weld bead characteristics in coating SS309L on carbon steel substrates by wire arc additive manufacturing (WAAM) and identifying the optimal parameters. The key parameters are current, travel speed, and voltage, while the weld bead characteristics include height, width, and depth of penetration. Experimental data and analysis of variance (ANOVA) are employed to develop and evaluate predictive models in Minitab software. The results show that the optimal process parameters for coating SS309L on carbon steel substrates by WAAM are voltage = 22 V, current = 132 A, and travel speed = 0.3 m/min, which improve height and width by 56.71% and 25.87%, respectively, while reducing the depth of penetration by 21.74% compared to the worst-case scenario.